الخصائص السيكومترية لمقياس إدمان الأنترنت لدى طلبة الجامعة من ذوي الإعاقة البصرية - غربي, جهاد; ساعد,شفيق (University of Eloued جامعة الوادي, 2024)
تطرق الباحثان في هذه الدراسة الى بناء مقياس إدمان الانترنت لدى طلبة الجامعة من ذوي الإعاقة البصرية، لما له من أهمية بالغة في استخدامه في شتى الدراسات والأبحاث العلمية التي تخص هاته الفئة، حيث عرض الباحثان المقياس على عدة خبراء ومحكمين متعددي التخصصات، وتم تطبيقه على عينة تتكون من (30) طالبا مكفوفا من جامعتي "الشهيد حمه لخضر بالوادي، وقاصدي مرباح بورقلة"، وذلك من أجل التأكد من الخصائص السيكومترية للمقياس، حيث استخدم الباحثان الصدق الظاهري والاتساق الداخلي لحساب الصدق، وكذلك استخدمت طريقة ألفا كرونباخ وطريقة التجزئة النصفية لحساب الثبات، وذلك بواسطة برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS). ومنه توصل الباحثان الى أن مقياس إدمان الأنترنت لدى الطلبة الجامعيين من ذوي الإعاقة البصرية يتمتع بدرجات صدق وثبات عالية وهو مؤهل لاستخدام في الدراسات والبحوث العلمية. Abstract: In this study, the researchers discussed the construction of a scale for Internet addiction among university students with visual disabilities, because of its great importance in using it in various studies and scientific research related to this group. The researchers presented the scale to several multidisciplinary experts and arbitrators, and it was applied to A sample consisting of (30) blind students from the universities of “Martyr Hama Lakhdar in El Oued and Kasidi Merbah Ouargla”, In order to ensure the psychometric properties of the scale, The researchers used the apparent validity and internal consistency to calculate the validity, and also used the Cronbach’s alpha method and the split-half method to calculate the reliability. Using the Statistical Package for the Social Sciences (SPSS) program. From this, the researchers concluded that the measure of Internet addiction among university students with visual impairment has high degrees of validity and reliability and is qualified for use in scientific studies and research.
Keywords: خصائص سيكومترية; إدمان الأنترنت; طالب كفيف; إعاقة بصرية; Psychometric properties; Internet addiction; blind student; visual impairment